(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The study was expected to discover the library security and client attitudes of the Regent University College of Science and Technology. The significant concern was to see if there were security issues in the library particularly with the utilization of books and other library material and the clients’ attitude towards the utilization and treatment of books. It was additionally to decide if rules and guidelines of the library were obeyed and whether clients obeyed security estimates set for the library.